245 GHz subharmonic receiver with on-chip antenna for gas spectroscopy application *Project supported by the Zhejiang National Natural Science Foundation of China (No. LQ17F040001) and the Key Laboratory Open Project Fund of Southeast University, China (No. K201817). (December 2018) - Mao, Yanfei; E, Shiju; Schmalz, Klaus; Christoph Scheytt, J.
Abstract: A 2nd transconductance subharmonic receiver for 245 GHz spectroscopy sensor applications has been proposed. The receiver consists of a 245 GHz on-chip folded dipole antenna, a CB (common base) LNA, a 2nd transconductance SHM (subharmonic mixer), and a 120 GHz push-push VCO with 1/64 divider. The receiver is fabricated in f T / f max = 300/500 GHz SiGe:C BiCMOS technology. The receiver dissipates a low power of 288 mW. Integrated with the on-chip antenna, the receiver is measured on-chip with a conversion gain of 15 dB, a bandwidth of 15 GHz, and the chip will be utilized in PCB board design for gas spectroscopy sensor application.